(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Tatyana B. Mikheeva, Margarita V. Ereschenko, Irina A. Antibas (Rostov-on-Don, Russian Federation) Understanding the interaction of actors in the process of dialogic communication is considered from the standpoint of teaching foreignlanguage dialogue and existing concepts of communicative strategies. The article presents specific features of the dialogue, as well as some defects in dialogical communication. Dialogue is seen as a phenomenon of oral, unprepared speech, reflecting all the laws of the process of communication as a whole. The unpreparedness of the act of dialogical communication is the foundation for the development of communicative competence in a foreign language. The need for the formation of communicative competence for the use of a foreign language in various spheres of human activity determines the attention paid by foreign language teachers and researchers to dialogue as the most common phenomenon of oral speech. For the collection and analysis of linguistic material, the methods of observation, experiment, and the method of extracted discourse were used. Particular attention is paid to the specifics of the grammatical design of the speaker’s intentions. In teaching the grammatical formulation of dialogical speech, the role strategies of communicants can be used. The authors propose the introduction of a module of a communicative workshop, where the simulated dialogue will serve as the main unit. Key words: dialogic communication, communicative strategies, modeling of linguistic interaction, grammatical design, communication defects.